Experimental Investigation of Coal Dust Wettability Based on Surface Contact Angle - Gang Zhou; Han Qiu; Qi Zhang; Mao Xu; Jiayuan Wang; Gang Wang (Journal of Chemistry)
Wettability is one of the key chemical properties of coal dust, which is very important to dedusting. In this paper, the theory of liquid wetting solid was presented firstly; then, taking the gas coal of Xinglongzhuang coal mine in China as an example, by determination of critical surface tension of coal piece, it can be concluded that only when the surface tension of surfactant solution is less than 45 mN/m can the coal sample be fully wetted. Due to the effect of particle dispersity, compared with the contact angle of milled coal particle, not all the contact angles of screened coal powder with different sizes have a tendency to increase. Furthermore, by the experiments of coal samples’ specific surface areas and porosities, it can be achieved that the volume of single-point total pore decreases with the gradual decreasing of coal’s porosity, while the ultramicropores’ dispersities and multipoint BET specific surface areas increase. Besides, by a series of contact angle experiments with different surfactants, it can be found that with the increasing of porosity and the decreasing of volume percentage of ultramicropore, the contact angle tends to reduce gradually and the coal dust is much easier to get wetted.